Association Between Psychiatric Disorders, Substance Use, and Sexual Risk Behaviors in Perinatally HIV‐Exposed Youth. (July 2018) - Benson, Stephanie; Elkington, Katherine S.; Leu, Cheng‐Shiun; Bucek, Amelia; Dolezal, Curtis; Warne, Patricia; Mellins, Claude
Abstract : N/A: As youth with perinatally acquired HIV infection age, there is a need for studies that identify predictors and correlates of sexual risk behaviors. We examined the association between psychiatric disorders and substance use disorders (SUD) with sexual risk behaviors in youth with perinatally acquired HIV infection and perinatally HIV‐exposed but uninfected youth. Participants were recruited from four medical centers in New York City. The Diagnostic Interview Schedule for Children and the Adolescent Sexual Behavior Assessment were administered to assess psychiatric disorders and sexual behaviors, respectively. SUD and behavior disorders were correlated with either ever having had penetrative sex or recent condomless sex for participants with perinatally acquired HIV infection only. Results suggest that clinicians should screen and treat patients for SUD and behavioral disorders to reduce sexual risk behaviors in youth with perinatally acquired HIV infection.